Pemberdayaan Perempuan melalui Perempuan Kepala Keluarga dalam Meningkatkan Ekonomi Keluarga - Siti Nurgina; Dadang Kuswana; Indira Sabet Rahmawaty (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2021)
This study aims to find out the background of the PEKKA program, the implementation of the program and the results of the PEKKA program on improving the family economy. The research method used is a qualitative method with descriptive research. The results showed that the background of the PEKKA program in the city of Sukabumi began with the adoption of the National Women's Commission program. However, in the City of Sukabumi, this program is aimed at women who want to try and develop to help with income in the family, whether women are widowed or who still have a husband with certain conditions. Implementation of activities in the form of trainings aimed at improving the family's economy. And the results of the PEKKA program on improving family economics are improving living standards, building critical awareness, and meeting family needs.